Peran Materialitas dalam Penentuan Sampling terhadap Efisiensi Waktu dan Ketepatan Audit pada Perusahaan Manufaktur - Rini Ika Wulandari; Nanda Wahyu Indah Kirana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The role of materiality in the audit process significantly affects the accuracy of sample selection and the efficiency of financial statement examination. Manufacturing companies, which often have high transaction volumes and complex recording systems, pose specific challenges for auditors, especially when constrained by limited time, personnel, and resources. Inaccurate determination of materiality thresholds or inappropriate sampling techniques may result in undetected material misstatements in the financial statements. The case of PT Indofarma Tbk, which caused a state loss of IDR 371.8 billion, illustrates weak internal controls and the suboptimal application of materiality and audit sampling, both of which undermined audit effectiveness and failed to identify high-risk areas. Therefore, careful determination of materiality levels is essential so that audit procedures can focus on high-risk areas. This study aims to explore how materiality is applied in determining audit samples and how it impacts the quality and efficiency of the audit. A descriptive qualitative approach was used, involving interviews, literature studies, and observation. The results indicate that the application of materiality in the audit process at PT ABC played a key role in improving time efficiency and the accuracy of financial examinations. Proper application of materiality and appropriate sampling strategies support auditors in working more effectively and in producing high-quality audit reports.